THE CHOICE OF MATERIAL AND HEAT TREATMENT REGIMES OF STEEL GRINDING BALLS, MEETING THE REQUIREMENTS OF THE MODERN - A. B. Sуchkov; A. B. Steblov; S. N. Berezov (Литьë и металлургия)
The task of this article is to choose effective chemical composition of the steel and heat treatment regime in the production of steel grinding balls.